Market Risk Management in Islamic Banking in Indonesia - Prawira, Anggun Wida (CV. Ulil Albab Corp, 2025)
This study aims to review various literature and empirical research results that discuss the relationship between market risk and the financial performance of Islamic banking in Indonesia. The results of the review show that market risk has a significant influence on profitability and investment returns, both directly and indirectly. However, there are still challenges in managing market risk, especially in terms of strengthening the risk management system in accordance with sharia principles. Therefore, the development of adaptive and sharia-based risk mitigation strategies is important to support the sustainability of Islamic banking amidst financial market volatility.